Associations between red cell distribution width and outcomes of adults with in-hospital cardiac arrest: A retrospective study. Issue 4 (28th January 2022) - Cheng, Yanwei; Peng, Hailin; Zhang, Jiange; Zhu, Juan; Xu, Lijun; Cao, Xue; Qin, Lijie
Abstract : Abstract: Previous studies found that high red cell distribution width (RDW) value is associated with poor outcomes among out-of-hospital cardiac arrest survivors. The aim of this study was to investigate whether post-ROSC RDW value was associated with survival and neurological outcomes of in-hospital cardiac arrest (IHCA) patients achieving return of spontaneous circulation (ROSC) but remaining critically ill. This retrospective single-center observational study included IHCA adults with sustained ROSC between January 1, 2017 and January 1, 2021 at an academic medical center in China. PostROSC RDW values were measured within 1 hour after sustained ROSC. The primary outcome was survival to hospital discharge and the secondary outcome was favorable neurological outcome at hospital discharge. The associations between postROSC RDW value and outcomes among IHCA patients with ROSC were evaluated by using multivariate logistic regression. A total of 730 patients with sustained ROSC following IHCA were ultimately included in this study. Of whom 194 (26.6%) survived to hospital discharge and 116 (15.9%) had a favorable neurological outcome at hospital discharge. In multivariable logistic regression analysis, lower postROSC RDW value was independently associated with survival to hospital discharge (odds ratio 0.19, 95% confidence interval 0.15–0.63, P = .017, cut-off value: 15.5%) and favorable neurological outcome at hospital discharge (odds ratio 0.23, 95% confidence interval 0.07–0.87, P < .001, cut-off value: 14.6%). Other independent factors including younger age, initial shockable rhythm, shorter total cardiopulmonary resuscitation duration and post-ROSC percutaneous coronary intervention were also associated with survival to hospital discharge. Regarding favorable neurological outcome at hospital discharge, significant variables other than the aforementioned factors included postROSC targeted temperature management and absence of pre-existing neurological insufficiency. Low postROSC RDW value was associated with survival to hospital discharge and favorable neurological outcome at hospital discharge.